Efektivitas Konseling Kelompok Dengan Teknik Cognitive Restructuring (CR) Untuk Menurunkan Perilaku Bullying Pada Siswa SMP Plus Nurul Hikmah Pamekasan - Iswatun Hasanah (Universitas Kanjuruhan Malang, 2018)
The purpose of this research is to know effectiveness of group counseling by using “cognitiverestructuring” technique to reduce “bullying” habit of the students of SMP Plus Nurul HikmahPamekasan. The subject of this research is the students of SMP Plus Nurul Hikmah Pamekasan whichis showing “bullying” Habit (N=6). The kind o the research that is used quasi experiment designed inOne Group pretest posttest design, it is an experiment that conducted only to one group withoutcompared group whit bullying scale as data collection instrument arranged by researcher based ontheory and has been tested for its validity and reliability. Data analysis that is used in this research isstatistic test wilcoxon and the result of this research that is done analyzed by using statistic testwilcoxon by value asymp sig=0,046 (coefficient level P<0,05) and Z arithmetic = 1,997 could beconcluded that a group counseling by using cognitive restructuring is effective to reduce bullyinghabit of SMP Plus Nurul Hikmah Pamekasan.